(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
The role of media personnel in spreading the knowledge about Child Rights cannot be under estimated in view of their very close contacts with people at all levels. A study is made on media personnel to know their level of knowledge and related issues of Child Rights Protection. Five hundred print media persons working in eight districts of Mysuru Revenue Division have been chosen for the study and they were administered a pre-tested questionnaire. The results indicate that the media personnel have knowledge in certain areas and are deficient in other areas. The role of media personnel, as change agents, has been explained.